PAID ADVERTISEMENTS AND THEIR IMPACT ON THE PURCHASING BEHAVIOUR OF SOCIAL MEDIA USERS IN JORDAN: DEMOGRAPHIC VARIABLE AS MODERATOR - Mustafa S. Al-Shaikh; Rania Ahmad Alqunbor; Abdalmuttaleb Al-Sartawi; Hebah Kamal Jamal (Fonseca, Journal of Communication, 2025)
The study aimed to examine the impact of demographic variables, such as educational qualifications, on the relationship between paid advertisements specifically advertisement design, content, and timing and purchasing behaviour among social media users in Jordan. An analytical descriptive methodology was employed, with data collected through a self-administered questionnaire. A sample of 290 participants was analysed using appropriate statistical techniques. The results revealed a statistically significant relationship between paid advertisements (including design, content, and timing) and purchasing behaviour, as well as a notable influence of demographic factors, such as educational qualifications, on this relationship. The study recommends that companies and decision-makers prioritise the advertising message and provide more detailed product information on social media platforms.